Electrospinning of poly(decamethylene terephthalate) to support vascular graft applications. (15th February 2022) - Van de Voorde, Babs; Sensu, Berna; De Vos, Lobke; Colenbier, Robin; Baskan, Havva; Geltmeyer, Jozefien; Parmentier, Laurens; Van Daele, Lenny; Dmitriev, Ruslan I.; Pyl, Lincy; De Clerck, Karen; Van Vlierberghe, Sandra
Graphical abstract: Highlights: Single-step solution polycondensation of poly(decamethylene terephthalate) Optimized electrospinning conditions for micro-sized PAT(n=10) fibers. Fiber morphology depending on polymer-related electrospinning parameters. Enhanced endothelial cell viability and proliferation for certain PAT(n=10) fiber morphologies. Abstract: Recently, poly(nonamethylene terephthalate) (PAT(n=9) ) and poly(decamethylene terephthalate) (PAT(n=10) ) gained increasing interest since it was reported to exhibit enhanced endothelial cell adhesion and viability compared to other poly(alkylene terephthalate) (PAT) analogues. Enhanced endothelial cell interactivity is of particular interest when targeting cardiovascular applications, more specifically, for creating synthetic vascular bypass grafts. In this study, the potential of PAT(n=10) to be applied as synthetic bypass graft has been further investigated. After a thorough physico-chemical characterization of the synthesized PAT(n=10), micro-sized fibers were processed via electrospinning. In a first part, the polymer-related parameters were investigated and optimized to obtain uniform beadless fibers. By changing the solution composition and device set-up, various fiber morphologies (i.e. random, aligned and porous fibers) were obtained and subjected to an in vitro biological evaluation with Human Umbilical Vein Endothelial Cells (HUVECs), while exploiting a clinically used synthetic graft (i.e. Dacron®) as benchmark. It was shown that the cells seeded onto all PAT(n=10) fibers exhibited a superior metabolic activity compared to Dacron after 7 days of culture, while aligned and porous fibers had a beneficial effect on the survival of HUVECs. This study is a first step towards the application of PATs as novel cardiovascular bypass graft, fabricated via electrospinning.